QUALITATIVE STUDIES IMPLEMENTATION OF SHIPPING RULE ENFORCEMENT ON THE FULFILLMENT OF MARINE TRANSPORTATION SAFETY EQUIPMENT ON MOTOR SAILING SHIPS (KLM) AT PAOTERE PORT MAKASSAR - Hadi Setiawan; Sukirno Sukirno; Vevianty D Hemeto (Jurnal Ekonomi, 2023)
Motor Sailing Ship is a type of ship that uses a sail and a motor (ship engine) as its propulsion. Work safety is work safety indicating a condition that is safe or safe from suffering, damage or loss in the workplace. The Safety Of Life At Sea (SOLAS) regulation is a regulation that regulates maritime and shipping safety. This study aims to describe a qualitative study of the implementation of shipping rules enforcement on the fulfillment of marine transportation safety equipment on Motor Sailing Ships (KLM) at the Paotere Port of Makassar. Makassar Paotere Port has the same characteristics to be used as a research sample at that location. Snowball Sampling is a technique of determining the sample which is initially small in number, then this sample is asked to choose its friends to be used as samples and so on, so that the number of samples increases. The data analysis method used in this research is data triagulation. The results showed the enforcement of shipping rules on the fulfillment of marine transportation safety equipment on Motor Sailing Ships (KLM) at the Makassar Paotere Port from the verification results of all data and the results of interviews had gone well. Although the implementation process still needs evaluation and improvement. For example, the fulfillment of safety equipment standards at KLM, KLM licensing documents for seaworthiness, KLM checking, and socialization to fishermen or KLM crews about sailing rules. In addition, the regulator must ensure that the standard procedure for implementing the shipping rules runs well. The need for outreach activities to fishermen and KLM crews to better understand shipping rules so that accidents at KLM can be minimized.